Ferulic Acid-Nicotinamide Cocrystal: Synthesis, Experimental, and Computation Study - Pujiono, Fery Eko; Ekowati, Juni; Amrillah, Tahta; Setyawan, Dwi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Ferulic acid-nicotinamide cocrystals have been successfully synthesized using the solvent evaporation method. In this case, nicotinamide which acts as a coformer is mixed with ferulic acid with a 1:1 molar ratio via dissolving process in ethanol. The obtained cocrystals were characterized through Differential Scanning Calorimetric (DSC), Powder X-Ray Diffraction (PXRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and computational analyses. The DSC characterization revealed distinct endothermic peaks at 99.5°C and 128.5°C with a W-shaped profile. This result is different from the thermal behavior of pure ferulic acid which indicates that the ferulic acid-nicotinamide cocrystal is successfully formed. This result is also supported by the PXRD result which reveals distinct peaks at 5.24°, 16.31°, and 34.69° belong to crystal deformation of ferulic acid cocrystal due to the coexistence of nicotinamide coformer. The FTIR data also further indicate the formation of cocrystals marked by the disappearance of the NH(v) functional group at 3400 cm−1 and the emergence of a fuse-like peak at around 1600 cm−1 corresponding to the C-O(v) and NH() functional groups. SEM analysis also demonstrated morphological differences between the obtained cocrystal with pure ferulic acid crystals. The pure ferulic acid crystals exhibit a rectangular shape, whereas the cocrystals display a sword-like morphology. The phenomenon of cocrystal formation was also studied using computational studies through Density Functional Theory (DFT) and Quantum Theory of Atoms in Molecules (QTAIM) which confirmed that the cocrystals were stabilized through intermolecular hydrogen bonding.